Entrepreneurship : Tradisi Warisan / Nur Syazana Ahmad Alimi ... [et al.] - Ahmad Alimi, Nur Syazana; Ma’amor, Nurul Hani; Mat Jasoh, Nur Azima; Mohd Jamil, Nursyazwani (2008)
Our company has been named by Tradisi Warisan Sdn. Bhd. The nature of our business is manufacture and distributes Terengganu traditional foods that are ‘Satar and Otak-otak’. The location of our company is at the Kampung Geliga, Kemaman. We rent the premise and our address is No. 1860-2, Warong Aziz Satar, Jin Kuala Kemaman, Kampung Geliga, 24000 Chukai, Kemaman, Terengganu Darul Iman.